The reorganisation of the curriculum in educational cycles in CODEMA College : a positive step and paintings in theirsteps fractals (2017)
ABSTRACT: The policy of reorganising schools in pedagogical cycles has been restored little by little in the state schools of the city of Bogota. This reform began in the year 2008 in CODEMA COLLEGE, which faced a number of challenges, personal as much as institutional. The reform depended upon the participation and engagement of the educational community in the reform process, and for that reason, this paper presents a positive view of the school reorganisation in relation to the theme of cycles, to balance some of the views that have been expressed previously.